2021
DOI: 10.3390/ijms22115788
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Biomarkers Associated with Age-Related Diseases and Current Methods for Glycan Analysis

Abstract: Ageing is a complex process which implies the accumulation of molecular, cellular and organ damage, leading to an increased vulnerability to disease. In Western societies, the increase in the elderly population, which is accompanied by ageing-associated pathologies such as cardiovascular and mental diseases, is becoming an increasing economic and social burden for governments. In order to prevent, treat and determine which subjects are more likely to develop these age-related diseases, predictive biomarkers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 235 publications
(412 reference statements)
3
19
0
Order By: Relevance
“…Here, we combined characterization of Hp types with peptide-centric glycoproteomics of isolated Hp protein from healthy donors’ sera to analyze the effect of Hp polymorphism on its glycosylation. Age, gender and underlying diseases are known to change protein glycosylation patterns [21] . To minimize such pre-analytical effects, we collected samples from age-matched healthy donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we combined characterization of Hp types with peptide-centric glycoproteomics of isolated Hp protein from healthy donors’ sera to analyze the effect of Hp polymorphism on its glycosylation. Age, gender and underlying diseases are known to change protein glycosylation patterns [21] . To minimize such pre-analytical effects, we collected samples from age-matched healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…The Hp glycosylation pattern has been reported to be altered in patients with many types of cancers, raising the interest of using it as a protein glycobiomarker for prognostic and diagnostic purposes [1] . For example, an increased level of N-glycan branching, sialylation and/or fucosylation of Hp has been reported for pancreatic [1] , [18] , [19] , [20] , hepatic [11] , [12] , [21] , lung [22] , [23] , colon [1] , [21] , [24] and ovarian [1] , [25] cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we also observed an increased expression of several O-linked glycosylation factors in the arteries and adipose tissue of old people, suggesting a role of this pathway in ageing-related alterations in these tissues. Previous works have also shown that ageing is associated with a decreased expression of several glycosylation factors in the brain [ 74 ]. Since most studies assessing ageing-related changes in glycosylation use blood derivatives (plasma, serum, immunoglobulin fractions), their applicability may be limited and overlook tissue-specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, glycosyltransferases have been shown to be useful in the classification and prognosis of certain cancers [ 77 ], where differences in the expression of sialyltransferases seem to be among the most relevant to distinguish different cancer types. An increase in sialylation has been reported in some tumor types, such as colorectal cancer [ 17 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before subjecting the samples to MS, some of them undergo release, separation, and enrichment for glycans [36]. Some reviews have specifically described the technical approaches for preparing such samples [37,38]. Due to the low abundance of glycoproteins and glycosylated peptides in the biological samples, a series of enrichment analyses are conducted before the analysis, such as lectin enrichment and hydrophilic affinity enrichment [39].…”
Section: Research Techniques Related To Glycosylation In Gynecologica...mentioning
confidence: 99%